Mentoring Of Documents Arrangement Of Educational Unit Accreditation Instrument 2020 In Preparation For School Accreditation - Simarmata, Justin Eduardo; Fitriani; Thaal, Pius (Talenta Publisher, 2022)
This community service aims at providing mentoring toward accreditation team in SDK Biloe in relation to school accreditation. School accreditation is a comprehensive assessment process of the feasibility of schools, the results of which are manifested in the form of public accountability carried out by an independent and professional institution, called BAN S/M. Assistance activities for the preparation of the 2020 Education Unit Accreditation Instrument Document (IASP) at SDK Biloe were carried out with the stages of preparation, mentoring, and reflection. The implementation of accreditation can be viewed from two things that are assessed, namely a review of administrative compliance and secondly related to the performance of the education unit for efficiency and simple and accountable implementation. After mentoring, it was found that there was an increase in the understanding and awareness of school principals, teachers, and education staff about accreditation which is one of the factors in improving the quality of education. The level of understanding is manifested by the preparation of complete documents referring to IASP 2020, namely documents on the components of graduate quality, quality of learning processes, quality of teaching staff, and quality of school management.